Avaliação da produção de sons de peixes teleósteos retidos em cercos-fixos de pesca artesanal em Ilha Comprida, SP, por meio de técnicas acústicas passivas - Pereira, Luiza Rossato [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Bony fish constitute the largest and most diverse group of vertebrates in existence, having a wide variety of mechanisms for sound generation, however, there are still mute species. Phonations consist of isolated pulses, pulse sequences or predominantly low frequency tonal sounds, in order to courtship behavior, aggressiveness, territoriality and stress response. The objective of this work was to evaluate the acoustic production of different species of fish contained in artisanal fishing enclosures, thus making it possible to distinguish them. The study took place in the Estuarine-Lagunar Region of Cananéia through the species retained in the fixed enclosures. The sounds were obtained from a digital recorder connected to a hydrophone, for 2 days, and the samples were analyzed using the Raven Pro 1.6 software. Three species were retained, being mullet (Mugil liza), sea bream (Anisotremus surinamensis) and paru (Chaetodipterus faber). More than 5,700 sound emissions were analyzed and these presented a pattern with eleven different dominant frequencies and four types of sounds. The Estuarine Lagunar Region of Cananéia contains ecosystems with great potential for research activities, such as fish bioacoustics, since most teleost species still do not have their acoustic repertoire described. Future research should focus on simultaneous environmental data collection with acoustic and laboratory analyzes to complement repertoire descriptions, as this would help explain the variability in fish sound production with respect to natural and anthropogenic influences.

Os peixes ósseos constituem o maior e mais diverso grupo de vertebrados existente, possuindo uma ampla variedade de mecanismos para a geração de som, porém, há ainda espécies mudas. As fonações consistem em pulsos isolados, sequências de pulsos ou sons tonais predominantemente de baixa frequência, a fim do comportamento de cortejo, agressividade, territorialidade e resposta ao estresse. O objetivo deste trabalho buscou avaliar a produção acústica de diferentes espécies de peixes contidos em cercos de pesca artesanal, possibilitando assim distingui-las. O estudo aconteceu na Região Estuarino-lagunar de Cananéia através das espécies retidas nos cercos fixos. Os sons foram obtidos a partir de um gravador digital conectado a um hidrofone, durante 2 dias, e as amostras analisadas no software Raven Pro 1.6 Foram retidas 3 espécies, sendo tainha (Mugil liza), sargo-de-beiço (Anisotremus surinamensis) e paru (Chaetodipterus faber). Mais de 5.700 emissões de sons foram analisados e estes apresentaram um padrão com onze frequências dominantes diferentes e quatro tipo de sons. A Região Estuarina Lagunar de Cananéia contém ecossistemas com muito potencial para atividades de pesquisa, como a bioacústica de peixes, uma vez que grande parte das espécies de teleósteos ainda não têm seu repertório acústico descrito. As pesquisas futuras devem se concentrar na coleta de dados ambientais simultâneos com análises acústicas e laboratoriais para complementar as descrições dos repertórios, uma vez que isso ajudaria a explicar a variabilidade na produção sonora dos peixes com relação às influências naturais e antropogênicas.
Evaluation of the production of teleoste fish sounds retained in fixed fishing seins in Ilha Comprida, SP, through passive acoustic techniques
Keywords: Biologia Marinha; Bioacústica; Peixes